Words putting pain in motion: the generalization of pain-related fear within an artificial stimulus category - Bennett, Marc P.; Meulders, Ann; Baeyens, Frank; Vlaeyen, Johan W. S. (Frontiers in Psychology, 2015)
Patients with chronic pain are often fearful of movements that never featured in painful episodes. This study examined whether a neutral movement’s conceptual relationship with pain-relevant stimuli could precipitate pain-related fear; a process known as symbolic generalization. As a secondary objective, we also compared experiential and verbal fear learning in the generalization of pain-related fear. We conducted an experimental study with 80 healthy participants who were recruited through an online experimental management system (Mage = 23.04 years, SD = 6.80 years). First, two artificial categories were established wherein nonsense words and joystick arm movements were equivalent. Using a between-groups design, nonsense words from one category were paired with either an electrocutaneous stimulus (pain-US) or threatening information, while nonsense words from the other category were paired with no pain-US or safety information. During a final testing phase, participants were prompted to perform specific joystick arm movements that were never followed by a pain-US, although they were informed that it could occur. The results showed that movements equivalent to the pain-relevant nonsense words evoked heightened pain-related fear as measured by pain-US expectancy, fear of pain, and unpleasantness ratings. Also, experience with the pain-US evinced stronger acquisition and generalization compared to experience with threatening information. The clinical importance and theoretical implications of these findings are discussed.